Unveiling Students' Understanding of Ammonia as a Weak Base through Scaffolding-Based Chemical Reasoning Assessment - Yuda Faturohman; Endang Susilaningsih; Harjono Harjono; Murbangun Nuswowati; Ella Kusumastuti; Dimas Gilang Ramadhani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Reasoning is a basic cognitive ability in science learning, especially in chemistry, in which students must connect macroscopic, symbolic, and microscopic levels. However, most students seem to have difficulty learning chemical reasoning, especially in the ionization of weak bases (examples: NH₃). This study uses a scaffold-based assessment to evaluate students' explanations for ammonia as a base. A paper-and-pencil test was applied to 91 first-year preservice chemistry students to test them on phenomenological, mechanical, and structural types of reasoning. Two raters rated responses, and scoring reliability was assessed using Cohen’s Kappa (0.925). The data analysis consisted of descriptive statistics, correlation analysis, clustering (K-Means and t-SNE), and regression prediction with XGBoost. The results demonstrate that structural reasoning exhibits the highest level, but phenomenological reasoning has the most variation. There appears to be a high correlation between phenomenological empirical generalization and structural reasoning (r = 0.35+). Clustering outputs show three categories of students: high (R3), moderate (R2), and low (R1) reasoning, and most of the students are categorized at the moderate reasoning level, indicating some misconceptions. The XGBoost model performs well in predicting high-reasoning students but not in the moderate-reasoning classification. This paper indicates the power of scaffolding-embedded assessment for deducing reasoning patterns and misconceptions in ammonia ionization. The results can guide adaptive learning approaches for improving students' chemical reasoning.